PERILAKU PETANI DALAM BUDIDAYA SAYUR BERDAUN HIJAU SELAMA MASA PANDEMI COVID-19 DI DESA MATA AIR KECAMATAN KUPANG TENGAH KABUPATEN KUPANG - Novita Irena Sari; Leta Rafael Levis; Sondang S. P. Pudjiastuti; Ignatius Sinu (Buletin Ilmiah Impas, 2022)
Research on farmer behavior in cultivating green leafy vegetables during the covid-19 in Mata Air Village Central Kupang District Kupang Regency was carried out in March 2022. The purpose of this study was to determine the behavior of farmers in cultivating green leafy vegetables during the covid-19 pandemic in Mata Air village and the factors that influence the behavior of farmers in cultivating green leafy vegetables during the covid-19 pandemic. The results showed that the behavior of farmers in cultivating green leafy vegetables during covid-19 pandemic was in the moderation, meaning that the behavior of farmers in carrying out a cultivation activity at the research 1 ovation was mediocre.. Factors that influence farmer behavior such as farmer satisfaction, government support, economic motivation, social motivation, environmental encouragement and the ease of obtaining innovation do not affect the behavior of fanners in Mata Air village in carrying out green leafy vegetables cultivation during the covid-19 pandemic.